Blended learning model for medical English: Enhancing self-regulated learning outcome - Chunmei, Liu (2025)
The Blended Learning (BL) approach has become the new norm in English for Medical Purposes (EMP) courses since the COVID-19 pandemic. Nevertheless, many EMP learners continue to face challenges with Self-Regulated Learning (SRL) in such contexts. This study adopted a mixed-methods design grounded in Richey and Klein's Design and Development Research (DDR) framework to construct a BL instructional model suited to the EMP context, embedding SRL theories and the Community of Inquiry (CoI) framework. During the needs analysis phase, both quantitative and qualitative data were collected to investigate EMP learners' needs, SRL challenges, and expectations for teacher support in BL contexts. In the design and development phase, guided by the ADDIE model, the study formulated instructional design principles incorporating SRL theories and the CoI framework. A tailored BL model for EMP instruction was developed, incorporating modular multimedia materials, interactive CoI-based activities, teacher-facilitated SRL guidance, and a blended format combining station rotation with flipped classroom approaches. The model was implemented over one semester to refine its design through iterative feedback. In the evaluation phase, expert validation was conducted using the Fuzzy Delphi Method. The results showed that students lacked effective SRL strategies and voiced a strong desire for structured guidance, peer interaction, and accessible resources in BL settings, while experts reached a strong consensus on the model's pedagogical merit and feasibility and emphasized the importance of addressing learner diversity in SRL support. This study provides meaningful implications for EMP educators and instructional designers, highlighting the value of theoretically informed and empirically validated BL models that foster students' SRL growth. The proposed model provides a practical framework for enhancing the effectiveness and sustainability of blended EMP courses in higher vocational education contexts.